MARS/NDRI/KSU Communications Workshop: Part 2. Complete Response Sets to Dhulikhel Conference Questions by Target Audience - Leslie, John F.; Harvey, Jagger J.W.; Morris, Jeffery B. (My University, 2022)
A. Consumers (7 pages) B. Producers, Traders & Distributors (15 pages) C. Health Professionals (3 pages) D. Educators, Trainers & Researchers (8 pages) E. Policy Makers & Regulators (12 pages)
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication